2013
DOI: 10.12693/aphyspola.124.772
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Charge Compensation of Heteropolar SiC/GaN Interfaces

Abstract: We present studies of the morphology and charge distribution at the 4H-SiC/wz-GaN heteropolar junctions. Our investigations are based on the rst principles calculations in the framework of the density functional theory where the interfaces between the SiC substrate and GaN layers are represented by means of a slab. These studies reveal possible charge compensation patterns at the interfaces that lead to charge redistribution from monopole to dipole character and increase the stability of the junctions. It turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…1-7 involving an appropriate exchange of 50% of N(B) atoms in the N(B) layer of the N(B)-C interface by B(N) atoms in the diamond/c-BN junction leads to stable, charge compensated interfaces. Our studies confirms general trend observed in heterovalent junctions (e.g., 4H-SiC/wz-GaN [11,12]) that charge compensating reconstruction of the interface is a prerequisite of its energetic stability.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1-7 involving an appropriate exchange of 50% of N(B) atoms in the N(B) layer of the N(B)-C interface by B(N) atoms in the diamond/c-BN junction leads to stable, charge compensated interfaces. Our studies confirms general trend observed in heterovalent junctions (e.g., 4H-SiC/wz-GaN [11,12]) that charge compensating reconstruction of the interface is a prerequisite of its energetic stability.…”
Section: Discussionsupporting
confidence: 90%
“…The cutoff of 400 Ry is used for the real space mesh. The Brillouin zone integrations are performed by means of the (11,11,11) and (9,9,9) k-points meshes for bulk diamond and boron nitride crystals, respectively, as well as the (5,5,1) one for superlattice calculations. The diamond and zinc-blende (c-BN) nitride crystals are represented by cubic supercells that are repeated periodically in space.…”
Section: Calculation Methods and Model Of C/c-bn Heterostructurementioning
confidence: 99%
“…Finally, charge transfer at C-N reconstructed interfaces in diamond/BN stacked along [111] lies at most in the increase in electron charge at the bonds joining the compensating C atom with the nearest neighbours, as well as in the increase in electron charge present in the boron and second substrate carbon monolayers. The results obtained for reconstructed interfaces of the (111)-C-N type, common in diamond/c-BN, 4H-SiC/GaN [9], 3C-SiC/GaN (not presented here), show that the charge compensation by means of C atoms is always energetically favorable in the nitride layer (with ∆H > 0), opposed to the reconstructed interfaces (111)-C-B and (111)-C-Ga. In our opinion it is a consequence of different charge transfer picture within atomic layers.…”
Section: Resultsmentioning
confidence: 74%
“…1 has been presented in [9] for the 4H-SiC/GaN heterostructure with analogous wurtzite structure. On this basis it can be concluded that in the case of abrupt C-B interface 1 out of 4B atoms in the lateral 2 × 2 unit cell should be replaced by 1C atom, whereas in the case of abrupt C-N interface the substitution involves 1N atom in the first nitrogen layer.…”
Section: Calculation Methods and Models Of Diamond/c-bn Heterostructurementioning
confidence: 99%
See 1 more Smart Citation